Epistemologi Pendidikan Islam Klasik: Integrasi Ta'lim, 'Aql, Dan 'Umrān Menuju Paradigma Pendidikan Berbasis Peradaban - Abdulloh Arif Mukhlas; Sutono; Mulyadi; Mohammad Syaiku; Mufarrohah; Triyono; Roudlotul Hikmah; Kartono; Ovi Faturrohman; Yeni Fatimah; Barudin; Muhammad Wihdatun Nafi’in; Siti Nurun Ni’mah; Ghofur (Jurnal Pendidikan Agama Islam Miazhar, 2026)
The epistemology of classical Islamic education through the integration of the concepts of ta'lim (education), 'aql (reason), and 'umrān (civilization) as a holistic paradigm in building a civilization-based education system. This qualitative study with a library research approach analyzes Ibn Khaldun's thoughts in Al-Muqaddimah and the classical Islamic epistemological framework based on revelation, reason, and empirical experience. The results show that the epistemology of classical Islamic education is hierarchical-integrative with revelation as the highest source that guides reason and experience. Ibn Khaldun positions ta'lim as a gradual process of forming reason, where educated reason (from the natural, experiential, to theoretical levels) becomes the foundation for the birth of civilized 'umrān. The integration of these three concepts produces an educational paradigm that balances intellectual, moral, and social dimensions, different from the modern dichotomous approach. Therefore, the epistemology of classical Islamic education through the ta'lim-'aql-'umrān framework is relevant to respond to the contemporary educational crisis characterized by the dichotomy of knowledge, the secularization of knowledge, and the weakening of adab. The implications of this research offer a theoretical foundation for the development of an Islamic education curriculum oriented towards the formation of civilized humans (al-insān al-kāmil) and the development of sustainable civilization.